GE_GERICHTE C/8003/2011 vom 6. September 2013 - GE Cour de justice (2013)
DILIGENCE; EFFICACITÉ; RÉSILIATION; RÉNOVATION D'IMMEUBLE; TRAVAUX D'ENTRETIEN(EN GÉNÉRAL); RÉSILIATION ANTICIPÉE | CO.257f.2; CO.257f.3; CO.271.1